2012
DOI: 10.1111/j.1365-2672.2012.05353.x
|View full text |Cite
|
Sign up to set email alerts
|

Medium-chain-length polyhydroxyalkanoate production by newly isolated Pseudomonas sp. TN301 from a wide range of polyaromatic and monoaromatic hydrocarbons

Abstract: Aims: The aim of this study was to convert numerous polyaromatic and monoaromatic hydrocarbons into biodegradable polymer medium-chain-length polyhydroxyalkanoate (mcl-PHA). Methods and Results: Using naphthalene enrichment cultivation method, we have isolated seven bacterial strains from the river sediment exposed to petrochemical industry effluents. In addition to naphthalene, all seven strains could utilize between 12 and 17 different aromatic substrates, including toluene, benzene and biphenyl. Only one is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
40
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(43 citation statements)
references
References 67 publications
(74 reference statements)
3
40
0
Order By: Relevance
“…, 11 weeks) for a non-contaminated inoculum source, such as domestic activated sludge, was sufficient to yield styrene-degrading bacteria with mcl-PHA accumulation properties, providing a relatively simple and fast enrichment strategy. The mcl-PHA detected in all groups comprised C 6 , C 8 , C 10 , and C 12 monomers (Table 1), which was consistent with previous findings (25, 27). Previous studies suggested that the bioconversion process may begin with the side-chain oxidation of styrene and β -oxidation to form acetyl-CoA through phenylacetaldehyde before acetyl-CoA enters the downstream de novo fatty acid synthesis pathway that generates PHA precursors of varying chain lengths for PHA polymerization (29).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…, 11 weeks) for a non-contaminated inoculum source, such as domestic activated sludge, was sufficient to yield styrene-degrading bacteria with mcl-PHA accumulation properties, providing a relatively simple and fast enrichment strategy. The mcl-PHA detected in all groups comprised C 6 , C 8 , C 10 , and C 12 monomers (Table 1), which was consistent with previous findings (25, 27). Previous studies suggested that the bioconversion process may begin with the side-chain oxidation of styrene and β -oxidation to form acetyl-CoA through phenylacetaldehyde before acetyl-CoA enters the downstream de novo fatty acid synthesis pathway that generates PHA precursors of varying chain lengths for PHA polymerization (29).…”
Section: Discussionsupporting
confidence: 92%
“…Aromatic-degrading and PHA-forming bacteria are generally isolated from petrochemical-contaminated sites or bioreactors treating petrochemical industrial effluents (13, 25, 26) because these pre-enriched sources are more likely to yield microorganisms that could break down petrochemical aromatics. In the present study, activated sludge from a water reclamation plant treating municipal wastewater and industrial activated sludge from a petrochemical wastewater treatment facility were tested as inoculum sources.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…3) Narancic et al, (2012) reported the conversion of a range of polyaromatic hydrocarbon compounds to medium chain length PHA. The bacterial strain Pseudomonas sp.…”
Section: Staphylococcus Pasteuri Rd2mentioning
confidence: 99%